Midterm Re-interventions and Survival After Endovascular Versus Open Repair for Ruptured Abdominal Aortic Aneurysm. Issue 6 (June 2015) - van Beek, S.C.; Vahl, A.; Wisselink, W.; Reekers, J.A.; Legemate, D.A.; Balm, R.; ,
Abstract : Objective: To compare the midterm re-intervention and survival rates after EVAR and OR for ruptured abdominal aortic aneurysms (RAAA). Methods: Observational cohort study including all consecutive RAAA patients between 2004 and 2011 in 10 hospitals in the Amsterdam ambulance region. The primary end point was re-interventions within 5 years of the primary intervention. The secondary end point was death. The outcomes were estimated by survival analyses, compared using the logrank test, and subsequently adjusted for possible confounders using Cox proportional hazard models. Re-interventions were estimated in all patients and in patients who survived their hospital stay. Results: Of 467 patients with a RAAA, 73 were treated by EVAR and 394 by OR. Five years after the primary intervention, the rates of freedom from re-intervention were 55% for EVAR (26/73, 95% CI: 41–69%) and 60% for OR (130/394, 95% CI: 55–66%) ( p  = .96). After adjustment for age, sex, comorbidity, and pre-operative hemodynamic stability, the risk of re-intervention was similar (HR 1.01, 95% CI: 0.65–1.55). The survival rates were 36% for EVAR (45/73, 95% CI: 24–47%) and 38% for OR (235/394, 95% CI: 33–43%) ( p  = .83). In 297 patients who survived their hospital stay, the rates of freedom from re-intervention were 66% for EVAR (15/54, 95% CI: 52–81%) and 90% for OR (20/243, 95% CI: 86–95%) ( p  < .01). After adjustment for age and sex, the risk of re-intervention was higher after EVAR (HR 0.27, 95% CI: 0.14–0.52). Conclusions: Five years after the primary intervention, endovascular and open repair for ruptured abdominal aortic aneurysm resulted in similar re-intervention and survival rates. However, in patients who survived their hospital stay the re-intervention rate was higher for EVAR than for OR.